Predicting cattle performance from mathematical models - Brent, B.E.; Chestnut, A.; George, P. (Kansas State University. Agricultural Experiment Station, 2011)
Tables based on a mathematical model are presented that allow cost of gains by steers at various weights to be calculated. An example illustrate how to use the tables to help with economic decisions.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Performance; Gain